2019
DOI: 10.1021/acs.langmuir.9b01981
|View full text |Cite
|
Sign up to set email alerts
|

Coordinatively Unsaturated Metal Site-Promoted Selective Adsorption of Organic Molecules on Supported Metal–Organic Framework Nanosheets

Abstract: Metal–organic frameworks (MOFs) are a class of customizable porous material, which have shown good performance in separation processes, because of their large surface area and molecular recognition property. Although the effects of chemical structure of MOFs on their separation performance were extensively studied, the exploration of their surface properties was still limited. This work demonstrated a MOF nanosheet with large amount of coordinatively unsaturated metal sites, Cu­(BDC) (copper­(II) benzenedicarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[5] Zhang et al then used similar CuBDC nanosheets to selectively bind larger organic dye molecules with electron donor moieties, such as methyl orange, to open PW sites (Figure 5a). [105] The authors also observed weaker binding in solvents with higher basicity, owing to the stronger MONsolvent interactions. However, the significant adsorption and selectivity was still observed, indicating the suitability of PW MONs for sensing such analytes.…”
Section: Small Moleculesmentioning
confidence: 98%
See 2 more Smart Citations
“…[5] Zhang et al then used similar CuBDC nanosheets to selectively bind larger organic dye molecules with electron donor moieties, such as methyl orange, to open PW sites (Figure 5a). [105] The authors also observed weaker binding in solvents with higher basicity, owing to the stronger MONsolvent interactions. However, the significant adsorption and selectivity was still observed, indicating the suitability of PW MONs for sensing such analytes.…”
Section: Small Moleculesmentioning
confidence: 98%
“…[7,106] UV-vis titrations were used to quantify the binding and MONs functionalised with pentyl chains were found to bind more strongly than those with methoxy-propyl chains, which was attributed to intramolecular binding of the oxygen lone pair. In a follow-up [105] Copyright 2019, American Chemical Society. b) The chemical structure of the Co(CNS) 2 (pyz) 4 unit used by Sun et al to construct their MON system, and the color displays of colloidal suspensions of these MONs in selected nonpolar, protonic, and polar solvents.…”
Section: Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs) possess unique properties that include high specific surface area, flexible structures, open metal sites, and high thermal stability, which explain their prospective use in gas storage and separation, adsorption, and many other fields. , Benefiting from a large specific surface area, high porosity, low density, structural variability, and chemical stability, MOFs are widely regarded as very promising adsorbents . However, in practical applications, MOFs exhibit some technical limitations such as particle agglomeration and difficulty in recycling .…”
Section: Introductionmentioning
confidence: 99%
“…However, the loading of MOFs on some untreated CelF (e.g., pulp fibers and cotton fibers) is generally low in amount and weak in binding affinity. Therefore, some studies were conducted to promote the loading of MOFs on CelF, to a certain extent, by means of carboxymethylation [ 21 , 22 ], atomic layer deposition [ 23 ], citric acid modification [ 24 ], (3-aminopropyl)triethoxysilane (APTES) and 3-glycidyloxypropyltrimethoxysilane (GPTMS) as connecting substances [ 25 , 26 , 27 ], polydopamine as an intermediate layer [ 20 ], etc. However, the degradation of CelF is inevitable during carboxymethylation, and atomic layer deposition has high requirements for equipment.…”
Section: Introductionmentioning
confidence: 99%